2015
DOI: 10.1108/ijge-07-2014-0021
|View full text |Cite
|
Sign up to set email alerts
|

Women and apparel entrepreneurship

Abstract: Purpose – The purpose of this study was to explore strategies used by successful female entrepreneurs to manage the challenges of running a small apparel business. Design/methodology/approach – A qualitative research design was used. Primary and secondary data were collected on small business in three countries: Russia, South Africa and Thailand. In-depth interviews were conducted with a total of 11 female small apparel business owners. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 51 publications
1
22
0
3
Order By: Relevance
“…Despite the female dominance in this field, research that examines women as apparel business owners remains under-examined in small business research (Hodges et al, 2015). This study also contributes to previous work (Hodges et al, 2015) that highlighted and demonstrated the importance of accounting as a challenge for female apparel entrepreneurs and documented their opportunities. Furthermore, this research provides the initial steps toward identifying entrepreneur experiences in mobile retailing.…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…Despite the female dominance in this field, research that examines women as apparel business owners remains under-examined in small business research (Hodges et al, 2015). This study also contributes to previous work (Hodges et al, 2015) that highlighted and demonstrated the importance of accounting as a challenge for female apparel entrepreneurs and documented their opportunities. Furthermore, this research provides the initial steps toward identifying entrepreneur experiences in mobile retailing.…”
Section: Discussionmentioning
confidence: 75%
“…Additionally, these findings contribute to an understanding of the challenges and opportunities of female entrepreneurs in the fashion and retailing industry (Hodges et al, 2015), particularly given their prevalence in the apparel industry (Collins, 2003). Despite the female dominance in this field, research that examines women as apparel business owners remains under-examined in small business research (Hodges et al, 2015).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations